Hederagenin Attenuates Cerebral Ischaemia/Reperfusion Injury by Regulating MLK3 Signalling - Yu, Hailong; Song, Lilong; Cao, Xiang; Li, Wei; Zhao, Yuanyuan; Chen, Jian; Li, Jun; Chen, Yingzhu; Yu, Wenkui; Xu, Yun (Frontiers in Pharmacology, 2020)
Cerebral ischaemia/reperfusion (CI/R) injury is a major challenge due to the lack of effective neuroprotective drugs. Hederagenin (HE) is the aglycone part of saponins extracted from Hedera helix Linné that has exhibited anti-apoptotic and anti-inflammatory effects; however, the role of HE in CI/R has not been elucidated. In this study, mice were intraperitoneally (i.p.) injected with HE (26.5, 53, or 106 μmol/kg body weight) for three days after middle cerebral artery occlusion (MCAO). Neural function and brain infarct volume were evaluated. HE treatment attenuated CI/R-induced apoptosis and inflammatory cytokine expression within the infarcted areas. HE treatment also decreased the activation of the MLK3 signalling pathway, which potentiates CI/R damage via the MAPK and NFκB pathways. Due to HE’s safety profile, it has potential to be used for the clinical treatment of ischaemic stroke.